Penganggaran sebagai Alat Strategis dalam Perencanaan dan Pengambilan Keputusan Bisnis - Mikhael Devid James Sirait; Ade Faisal; Muhammad Alhadad; Masykur Arief Subagya; Abi Alpa Rijki; Muhamad Syahwildan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In today's competitive and dynamic business world, budgeting is no longer viewed solely as an administrative tool but has evolved into a crucial strategic instrument for organizational planning and decision-making. This study aims to explore the strategic role of budgeting in supporting the achievement of organizational goals, particularly through the alignment of short-term and long-term strategies. The method used is a literature study by examining various financial management theories and budgeting practices in several industrial sectors. The results of the study indicate that strategic budgeting can provide clear direction in resource allocation, organizational priority setting, and performance evaluation. In addition to being a control tool, the budget also functions to strengthen coordination between work units and support data-based decision-making. The participation of various stakeholders in the budgeting process plays a crucial role in increasing accountability, transparency, and a sense of ownership in achieving organizational goals. The integration of budget and strategy enables organizations to be more adaptive and responsive to the dynamics of the external environment. Thus, a flexible and participatory budgeting approach is essential so that the budget is not merely a static document but also a dynamic tool in supporting sustainable competitive advantage. This research concludes that strategically oriented budgeting significantly contributes to organizational effectiveness and success in achieving long-term goals.